Interobserver variation among pathologists and refinement of criteria in distinguishing separate primary tumors from intrapulmonary metastases in lung - Nicholson, Andrew; Warth, Arne (Journal of thoracic oncology, 2018)
Multiple tumor nodules are seen with increasing frequency in clinical practice. On the basis of the 2015 WHO classification of lung tumors, we assessed the reproducibility of the comprehensive histologic assessment to distinguish second primary lung cancers (SPLCs) from intrapulmonary metastases (IPMs), looking for the most distinctive histologic features. An international panel of lung pathologists reviewed a scanned sequential cohort of 126 tumors from 48 patients and recorded an agreed set of histologic features, including tumor typing and predominant pattern of adenocarcinoma, thereby opining whether the case was SPLC, IPM, or a combination thereof.
Available online: 7 November 2017
Gesehen am 13.09.2018